(untitled) (KULT_online, 2020)
Mikhail Minakov’s book Development and Dystopia: Studies in Post-Soviet Ukraine and Eastern Europe sheds new light on Ukraine’s post-soviet and most recent development by using an innovative approach, which combines philosophical reflections and data-rich empirical research. In four thematic sections, the study covers topics ranging from the historical evolvement of oligarchic groups, systemic corruption, and the role of ‘dystopian’ language in the public sphere to geopolitical imaginaries of (Anti)-Maidan protesters. Being an involved observer, the author provides timely analysis and convincingly succeeds in situating the Ukrainian case within broader philosophical and theoretical debates.